Bumblebee resilience to climate change, through plastic and adaptive responses. (30th June 2021) - Maebe, Kevin; Hart, Alex F.; Marshall, Leon; Vandamme, Peter; Vereecken, Nicolas J.; Michez, Denis; Smagghe, Guy
Abstract: Bumblebees are ubiquitous, cold‐adapted eusocial bees found worldwide from subarctic to tropical regions of the world. They are key pollinators in most temperate and boreal ecosystems, and both wild and managed populations are significant contributors to agricultural pollination services. Despite their broad ecological niche at the genus level, bumblebee species are threatened by climate change, particularly by rising average temperatures, intensifying seasonality and the increasing frequency of extreme weather events. While some temperature extremes may be offset at the individual or colony level through temperature regulation, most bumblebees are expected to exhibit specific plastic responses, selection in various key traits, and/or range contractions under even the mildest climate change. In this review, we provide an in‐depth and up‐to‐date review on the various ways by which bumblebees overcome the threats associated with current and future global change. We use examples relevant to the fields of bumblebee physiology, morphology, behaviour, phenology, and dispersal to illustrate and discuss the contours of this new theoretical framework. Furthermore, we speculate on the extent to which adaptive responses to climate change may be influenced by bumblebees' capacity to disperse and track suitable climate conditions. Closing the knowledge gap and improving our understanding of bumblebees' adaptability or avoidance behaviour to different climatic circumstances will be necessary to improve current species climate response models. These models are essential to make correct predictions of species vulnerability in the face of future climate change and human‐induced environmental changes to unfold appropriate future conservation strategies. Abstract : Bumblebees, cold‐adapted eusocial bees, are key pollinators in most temperate and boreal ecosystems, and significant contributors to agricultural pollination services. Despite the broad ecological niches occupied by many bumblebee species, the majority are threatened by climate change. In this review, we provide an in‐depth and up‐to‐date review on the various ways by which bumblebees overcome the threats associated with climate change at each of the different stages during their lifecycle and speculate to what extent bumblebees' capacity to disperse and track suitable climate conditions may influence possible adaptive responses.